Neurotransmitter metabolites in milk ferments of Leuconostoc mesenteroides regulate temperature-sensitive heartbeats in an ex ovo model - Mengke Zhang; Qing Chi; Mengru Lu; Jie Tang; Mingyu Zhang; Qianqian Wang; Deron R. Herr; Qing-Gao Zhang; Chun-Ming Huang (Heliyon, 2024)
Accumulated evidence has supported the probiotic activity of Leuconostoc mesenteroides (L. mesenteroides) which can yield beneficial metabolites via fermentation. Here, bovine milk rich in phenylalanine（PHE) was used as a source for fermentation of L. mesenteroides. The complexes of PHE with bacterial phenylalanine hydroxylase (PheH) at two temperatures were revealed via molecular dynamics simulation. Two carbon hydrogen bonds and a Pi-Alkyl T-shaped interaction were newly formed at an active site of the PheH-PHE complex. The PheH interacted with two different hydrogen atoms in an amine of PHE via conventional hydrogen bonds at 37 °C, a temperature that accelerated the milk fermentation of L. mesenteroides. Twenty-eight metabolites including various neurotransmitters in fermented milk were identified and quantified by liquid chromatography coupled to quadrupole ion trap (Q-Trap) tandem mass spectrometry. Ex ovo injection of milk ferments into the yolk sac of chicken embryos enhanced a rising temperature-induced increase in heartbeats towards the normal resting level. The neurotransmitter-rich milk ferments hold potential for using to adjust energy metabolism, referred from heart rates, during fluctuating temperature conditions.